Biodegradable esophageal stents in benign and malignant strictures – a single center experience - Sigounas, Dimitrios E.; Siddhi, Sandeep; Plevris, John N. (Endoscopy International Open, 2016)
Background and study aims: Biodegradable (BD) esophageal stents were recently developed mainly for refractory benign strictures, but experience and available literature are limited. Patients and methods: This was a retrospective observational study. All patients who had BD stents inserted due to refractory benign esophageal strictures or malignant strictures, or were awaiting radical radiotherapy/chemotherapy or neo-adjuvant therapy and esophagectomy between March 2011 and July 2015 were included.Results: Stent placement was successful in all patients. Ten patients with benign strictures (3 male, median age 80.5 years, IQR: 68.75 – 89.5) were followed-up for a median of 171.5 weeks (IQR: 24 – 177.25). The interval between dilatations prior to the first BD stent placement (median: 34.25 days, IQR: 23.06 – 48.29) was significantly shorter than the interval between the first BD stent placement and the first intervention required (median: 149.5 days, IQR: 94.25 – 209.5) and this difference was statistically significant (P = 0.012). Ten patients with esophageal cancer (8 male, median age: 69 years, IQR: 59.25 – 80.75) were included and they were followed up for a median of 36 weeks (IQR: 26 – 58). Only 1 completed radical radiotherapy successfully, but developed refractory post-radiotherapy stricture. No one proceeded to esophagectomy and 50 % required a self-expanding metal stent (SEMS) at a median of 134 days (IQR: 100 – 263) following stent placement.Conclusions: BD stents were successfully deployed in both benign and malignant strictures. They offered a prolonged dilatation-free interval in benign strictures, yet in the majority of patients, strictures recurred. In malignant strictures, stent patency was similar to that of benign strictures, which suggests a potential value in ensuring adequate oral intake during oncologic therapy. In our cohort, however, use of stents did not contribute to improved outcome.